PENGARUH TINGKAT SUKU BUNGA. BIAYA OPERASIONAL, PENDAPATAN OPERASIONAL DAN CAPITAL ADEQUANCY TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR PADA BEI 2021-2024 - Putri patresia br Tarigan; Nisya Elly Aprina br Ginting; Benny Rojeston Marnaek Nainggolan; Dokman Marulitua Situmorang (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
Banking companies function as financial institutions that offer various services, including fundraising, lending, and various other financial services to support economic growth. In this highly regulated sector, banks are required to maintain financial stability, run operations efficiently, and build client trust through proper risk management. The purpose of this study is to analyze the impact of price volatility, operating costs, laboratory operations, and capital tilt on profitability. This study uses 76 stocks from the Indonesia Stock Exchange as samples to conduct regression analysis. The results of this study indicate that economic growth is positively influenced by several variables, including interest rates, operating costs, operating profits, and capital ratios. The findings of this study indicate that several financial factors, such as interest rates, operating costs, laboratory operations, and capital recurrence ratios, have a significant impact on bank profitability. This concept emphasizes the need for efficient money management in increasing productivity and profits.